TGF-β1 on induced osteogenic differentiation of human dermal fibroblast - Aloise,Antonio Carlos (2014)
PURPOSE: To evaluate the role of transforming growth factor beta 1 (TGF-β1) on the induced osteogenic differentiation of human dermal fibroblasts. METHODS: We performed four groups with cultured dermal fibroblasts according to the culture medium: CONTROL (DMEM culture medium); TGF-β1 (DMEM culture medium with 10 ng/ml of TGF-β1); OSTEOG (DMEM culture medium with 0.5 µg/ml of ascorbic acid, 10 mmol/l of β-glycerophosphate and 10 nmol/L of dexamethasone); and OSTEOG/TGF-β1 (osteogenic medium with 10 ng/ml of TGF-β1). Alkaline phosphatase (ALP) activity and the amount of osteocalcin (OC) in the supernatant, as well as the capability to form calcium phosphate deposits, were analysed for 28 days RESULTS: There were significant differences (p<0.05) between CONTROL and TGF-β1 groups in comparison with OSTEOG and OSTEOG/TGF-β1 groups in the ALP activity and OC amount. Although, both osteogenic groups had the same behavior with regard the expression curve during the experimental time, the OSTEOG/TGF-β1 group achieved significantly higher ALP and OC levels and showed no significant difference in the levels of mineralized deposits and in comparison with the levels found in the OSTEOG group. CONCLUSION: The addition of transforming growth factor beta 1 to the osteogenic culture medium increased the activity of alkaline phosphatase and the amount of osteocalcin, but TGF-β1 did not alter the presence of mineralized calcium phosphate deposits.